Perancangan OLLA (Online Learning Lecturer Assistance): Model E-Learning Interaktif Pengganti Kuliah Tatap Muka - Syefrida Yulina; Dahliyusmanto - (RJOCS (Riau Journal of Computer Science), 2016)
In the field of E-learning systems, several systems have been used in order to support learning processes. But lack of university creates a virtual environment as substitute learning process. By using several interactive concepts, in this paper we propose the framework of OLLA (Online Learning Lecturer Assistance). In this framework, the instructors deliver the lectures, gives assignment after the class, the interaction and learning continue in an online discussionforum where members from a class can participate.